Az Emberi Jogok Európai Egyezménye 6. cikk 1. bekezdésének általános áttekintése az Emberi Jogok Európai Bíróságának gyakorlatára tekintettel - Rónai, Orsolya (Debreceni Jogi Műhely, 2014)
The most important human rights were firstly defined by the French Declaration from 1789. These rights are called as first generation rights, because they guarantee the most important civil and political rights of people. The states mostly act passive in order to protect them. They create acts on their protection, special mechanisms for enforcing them. We can state that every field of law is based upon them and helps protecting the human rights.The right to a fair trial is a first generation human right. Its regulation scheme is very complex; therefore it is a hard and a complex task to define the importance and the key functions of this right, because the laws on it are varied. Besides civil procedural law, international law, EU-law and – within national legal systems – constitutional law has also been dealing with the right to a fair trial.In the field of international law many international and regional treaties exist on the enforcement of procedural rights. In my paper I examined the European Convention on Human Rights (hereinafter: ECHR). The ECHR is an international treaty on the protection of human rights. It was born under the auspices of the Council of Europe in 1950, Rome. From 1959 its control mechanism is the European Court of Human Rights.In my paper I examined the proper interpretation and the actual application of the ECHR art. 6. par. 1based on the work of the international court.The article 6 of ECHR is about the right to a fair trial. In par. 1 the Convention gives a list of the most common features of a fair trial: (1) a fair and public hearing; (2) with a reasonable time; (3) the tribunal must be established by law and must meet with the requirements of independency and impartiality; (4) and finally the judgement shall be pronounced publicly. It enshrines the principle of the rule of law, upon which such a society is based and built.The first chapter deals with problem of the interpretation of the article. I tried to give the most convenient statements, which I defined upon the case law of the ECHR. After the question of interpretation is answered, the third chapter tries to give an overview of the applicability of article 6.In this section I cited many cases of the ECHR, because the Court has been developing the question of applicability in its case law. It is because it considers the Convention as a living-organism, so the article 6. needed to be interpreted again and again during these decades.